Moral distress: A review of the argument-based nursing ethics literature. (February 2015) - McCarthy, Joan; Gastmans, Chris
Aim: The aim of this review is to examine the ways in which the concept of moral distress has been delineated and deployed in the argument-based nursing ethics literature. It adds to what we already know about moral distress from reviews of the qualitative and quantitative research. Data sources: CINAHL, PubMed, Web of Knowledge, EMBASE, Academic Search Complete, PsycInfo, Philosophers' Index and Socindex. Review methods: A total of 20 argument-based articles published between January 1984 and December 2013 were analysed. Results: We found that like the empirical literature, most authors in this review draw on Jameton's original definition and describe moral distress in psychological–emotional–physiological terms. They also agree that moral distress is linked to the presence of some kind of constraint on nurses' moral agency, and that it is best understood as a two-staged process that can intensify over time. There is also consensus that moral distress has an important normative meaning, although different views concerning the normative meaning of moral distress are expressed. Finally, the authors generally agree that moral distress arises from a number of different sources and that it (mostly) affects negatively on nurses' personal and professional lives and, ultimately, harms patients. However, despite this consensus, many authors take issue with the way in which moral distress is conceptualized and operationalized. Moreover, while some worry that identifying nurses as a group of health professionals whose voices are ignored or marginalized might disempower nurses and encourage them to avoid their moral responsibilities, others take situations involving moral distress as indicative of more fundamental, structural inequities at the heart of contemporary healthcare provision. Conclusion: We conclude that research on moral distress in nursing is timely and important because it highlights the specifically moral labour of nurses. However, we suggest that significant concerns about the conceptual fuzziness and operationalization of moral distress also flag the need to proceed with caution.